The Relationship Between Coping Strategies And Maternal Self-Confidence In Mothers With Postnatal Depression - sofie azzahra aliyya (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Postnatal mothers are susceptible to depression due to various changes they experience after childbirth. Therefore, adopting appropriate coping strategies is essential to reduce the risk and symptoms of depression. This study aims to examine the relationship between coping strategies and maternal self-confidence in mothers with postnatal depression. A total of 40 mothers with postnatal depression in Banda Aceh were involved as research samples selected using the quota sampling technique. Mothers who are categorized as experiencing depression are mothers who obtain an EPDS score above 6. Data collection for the study used the Brief Cope scale, the K-D-M scale, and the Edinburgh Postnatal Depression Scale (EPDS), which were analyzed using Jeffrey's Amazing Statistics Program. The results of the hypothesis test analysis using Pearson's Correlations indicated a significant relationship between problem-focused coping and maternal self-confidence in mothers with postnatal depression, r=.34, p=.032. In contrast, no significant relationship between emotion-focused coping and maternal self-confidence, r=.08, p=.607. The results of the chi-square test analysis showed that age is a demographic factor that contributes to this study, particularly in relation to the level of maternal self-confidence in mothers with postnatal depression.Abstrak: Ibu pascamelahirkan rentan mengalami depresi dikarenakan banyaknya perubahan yang ibu alami pascamelahirkan, sehingga ibu perlu melakukan strategi koping yang tepat untuk mengurangi risiko dan gejala dari depresi yang dialami. Strategi yang dapat ibu gunakan untuk mengurangi symptom depresi ialah problem focused coping atau emotional focused coping. Penelitian ini bertujuan untuk mengetahui hubungan antara strategi koping dengan kepercayaan diri maternal pada ibu yang mengalami depresi pascamelahirkan. Sebanyak 40 ibu yang mengalami depresi pasca melahirkan di Banda Aceh terlibat sebagai sampel penelitian yang dipilih dengan teknik quota sampling, ibu dengan depresi pascamelahirkan adalah ibu yang memperoleh skor EPDS diatas 6. Pengumpulan data penelitian menggunakan skala Brief Cope, skala K-D-M, dan Edinburgh Postnatal Depression Scale (EPDS), yang dianalisis menggunakan Jeffreys Amazing Statistics Program. Hasil analisis uji hipotesis menggunakan Pearsons Correlations menunjukkan adanya hubungan yang signifikan antara problem focused coping dengan kepercayaan diri maternal pada ibu yang mengalami depresi pascamelahirkan, r=.34, p=.032. Sebaliknya, tidak ada hubungan yang signifikan antara emotional focused coping dengan kepercayaan diri maternal pada ibu yang mengalami depresi pascamelahirkan, r=.08, p=.607. Hasil analisa uji chi-square menunjukkan bahwa usia menjadi faktor demografi yang berkontribusi dalam penelitian ini yakni terhadap tingkat kepercayaan diri maternal pada ibu depresi pascamelahirkan.